Streptococcus pseudopneumoniae: Use of Whole-Genome Sequences To Validate Species Identification Methods - Jensen, Christian Salgård (J Clin Microbiol, 2021)
A correct identification of Streptococcus pseudopneumoniae is a prerequisite for investigating the clinical impact of the bacterium. The identification has traditionally relied on phenotypic methods. However, these phenotypic traits have been shown to be unreliable, with some S. pseudopneumoniae strains giving conflicting results. Therefore, sequence-based identification methods have increasingly been used for identification of S. pseudopneumoniae. In this study, we used 64 S. pseudopneumoniae strains, 59 S. pneumoniae strains, 22 S. mitis strains, 24 S. oralis strains, 6 S. infantis strains, and 1 S. peroris strain to test the capability of three single genes (rpoB, gyrB, and recA), two multilocus sequence analysis (MLSA) schemes, the single nucleotide polymorphism (SNP)-based phylogeny tool CSI phylogeny, a k-mer-based identification method (KmerFinder), average nucleotide identity (ANI) using fastANI, and core genome analysis to identify S. pseudopneumoniae. Core genome analysis and CSI phylogeny were able to cluster all strains into distinct clusters related to their respective species. It was not possible to identify all S. pseudopneumoniae strains correctly using only one of the single genes. The MLSA schemes were unable to identify some of the S. pseudopneumoniae strains, which could be misidentified. KmerFinder identified all S. pseudopneumoniae strains but misidentified one S. mitis strain as S. pseudopneumoniae, and fastANI differentiated between S. pseudopneumoniae and S. pneumoniae using an ANI cutoff of 96%.